Relationships between alexithymia and food addiction: The Finnish version of Yale Food Addiction Scale and preliminary test of its psychometric properties - Li, Ru; Kajanoja, Jani; Tuulari, Jetro J.; Karlsson, Linnea; Karlsson, Hasse; Karukivi, Max (Frontiers in Psychology, 2023)
Background: It has long been suggested that addictive behaviors are associated with alexithymia, a personality trait characterized by difficulties in emotional awareness and expression. However, little is known about the role of alexithymia in food addiction. Objectives: The aim of this study was to investigate the relationship between alexithymia and food addiction. As part of the study, the validity of the Finnish version of Yale Food Addiction Scale (YFAS-F) was also investigated. Methods: The sample consisted of 360 parents from the FinnBrain Birth Cohort Study. The structural validity of the YFAS-F was evaluated by confirmatory factor analysis (CFA). Exploratory factor analysis (EFA) was used to explore the structure when proposed models were not supported by CFA. The associations of alexithymia as measured by the 20-item Toronto Alexithymia Scale and food addiction were examined using regression analyses followed by structural equation modeling. Results: Higher alexithymia was associated with more food addiction by conducting linear regression analysis (B = 0.013, p = 0.011) and structural equation modeling (β = 0.24, p < 0.001). Furthermore, a single-factor model for the 8 criteria of the YFAS-F was supported by CFA and showed acceptable internal reliability (KR-20 = 0.72), and a three-factor solution for the 20 items of the scale was suggested by EFA with good internal reliability (McDonald’s ω = 0.91 for the YFAS-F, 0.91 for component 1, 0.87 for component 2, and Spearman-Brown coefficient = 0.89 for component 3). Conclusion: The current study determined a significant relationship between alexithymia and food addiction, which suggests alexithymia as a relevant factor for food addiction and may provide clinical implications for interventions. Moreover, the YFAS-F appeared to be a valid and reliable tool to evaluate food addiction in our Finnish general population sample. Further studies on the psychometric properties of the YFAS-F in more diverse populations are recommended.